Laser heat-mode patterning with improved aspect-ratio. (1st November 2021) - Zhang, Kui; Wang, Zhengwei; Chen, Guodong; Zheng, Jinlun; Mo, Zhichang; Wang, Yang; Wei, Jingsong
Abstract: Heat-mode lithography has received much attention owing to its capacity of breaking through the diffraction limit and realizing nano-patterning. However, the relatively lower aspect ratio of patterns seriously limits its scope of applications. In the currently available literature, the aspect ratio of submicron structures prepared by this method is less than 0.3:1. In this work, a new two-step development process was proposed to considerably improve the aspect-ratio of micro/nanostructures in the AgInSbTe (AIST) heat-mode resist. An aspect ratio of 1:1 can be kept even for the grating structures with a linewidth/period of 200nm/400 nm. The developed patterns can be transferred to silicon substrates with high fidelity. This simple and effective technique addresses key issues of heat-mode lithography in the manufacture of functional nanostructures requiring high aspect ratio, such as photomasks, templets of nanoimprint, and so on. Graphical abstract: Image 1 Highlights: A novel two-step development process is proposed for heat-mode lithography. The aspect-ratio of the micro/nanostructures in a heat-mode resist is enhanced. The depth profile of the crystallized domains is characterized layer by layer. The developed patterns are transferred onto Si substrates with high fidelity.